Percepções de trabalhadores rurais diagnosticados com cânceres linfohematopoiéticos sobre suas exposições ocupacionais e ambientais a agrotóxicos no semiárido cearense - Áfio, Neide da Silva (2024)
Pesticides can cause various effects on human health. Poisoning may occur acutely, with evident signs and symptoms in a short period, or chronically, resulting from continuous or intermittent exposure over extended periods. Among the diseases associated with chronic exposure, cancer stands out. Aiming to analyze the perceptions of rural workers diagnosed with lymphohematopoietic cancers (multiple myeloma, leukemias, non-Hodgkin lymphoma) regarding their occupational and environmental exposures to pesticides in the semi-arid region of Ceará, Brazil, we conducted a qualitative study. The study included 20 participants, all of whom had worked exclusively in agriculture throughout their entire lives for consecutive years. Additionally, the interviewees represented all five Health Regions of the state of Ceará. Data collection was carried out through in-depth interviews. After complete transcription, we employed Discourse Analysis as described by Minayo. For interpretation, we adopted Thompson's Depth Hermeneutics framework, which comprises three phases: socio-historical analysis, formal or discursive analysis, and interpretation/reinterpretation. The interviewees' accounts revealed experiences of successive exposures and poisonings, characterized as acute, and their perception of the "accumulation" of these chemical substances in their bodies due to daily exposure. This accumulation was perceived as a contributing factor to their development of lymphohematopoietic cancers. Our research also highlighted the participants' multiple exposures to different ingredients and active principles used in their routine activities, both in agriculture and dairy farming. Some of the substances mentioned are classified by international agencies, such as the IARC and USEPA, as highly toxic and potentially carcinogenic, including glyphosate, the most widely used pesticide worldwide. In this context, pesticide exposure and cancer development are understood as a chronic and social process resulting from reliance on a chemical-dependent production system. Structural changes are essential to integrate economic development reorientation with a stronger role for the health sector in promoting health and protecting life, involving greater participation of rural workers and strengthening cross-sectoral initiatives.